Economics and its enemies : - Coleman, William Oliver (Palgrave Macmillan, 2002)
Anti-economics is described as the opposition to the mainstream of economic thought that has existed from the 18th century to the present day. This book tells the story of anti-economics in relation to Smith, Ricardo, Mill, Walras, Keynes, and Hicks as well as current economic thinkers. William Coleman examines how anti-economics developed from the Enlightenment to the present day and analyzes its various guises; Right anti-economics, Left anti-economics, Nationalist and Historicist anti-economics and Irrationalist, Moralist, Aesthetic, and Environmental anti-economics.